2020
DOI: 10.26633/rpsp.2020.68
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship in hospitals in Latin America and the Caribbean: a scoping review

Abstract: Objectives. To examine published antimicrobial stewardship (AMS) initiatives in hospitals in Latin America and the Caribbean (LAC) in order to characterize AMS terminology usage, geotemporality, and elements of structure (human resources), process (interventions), and outcomes, and to set priority areas for improving AMS reporting. Methods. This was a scoping review that searched PubMed, LILACS, EMBASE, and 12 other databases, along with a manual search for academic and grey literature to identify documents on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…A recently published scoping review on ASPs in Latin America showed that although utilization of antimicrobials was the most frequently reported outcome, most studies had been done by measuring DDDs and only a few through a PPS. 15 During recent years, multicountry studies, such as the Global-PPS of antimicrobial consumption, 5 which included 4122 patients from 21 hospitals in Argentina, Chile, Costa Rica and Brazil, and a PPS on healthcare-associated infections (HAIs) and antimicrobial consumption including 2740 patients from 11 hospitals from four Latin American countries—Brazil, Colombia, Mexico and Venezuela—were conducted. 16 …”
Section: Introductionmentioning
confidence: 99%
“…A recently published scoping review on ASPs in Latin America showed that although utilization of antimicrobials was the most frequently reported outcome, most studies had been done by measuring DDDs and only a few through a PPS. 15 During recent years, multicountry studies, such as the Global-PPS of antimicrobial consumption, 5 which included 4122 patients from 21 hospitals in Argentina, Chile, Costa Rica and Brazil, and a PPS on healthcare-associated infections (HAIs) and antimicrobial consumption including 2740 patients from 11 hospitals from four Latin American countries—Brazil, Colombia, Mexico and Venezuela—were conducted. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, despite the repetitive calls for better antimicrobial stewardship, the adoption of ASPs is still lagging behind, particularly in regions with a high burden of antimicrobial resistance, such as the Middle East [ 6 , 20 ]. Latin America [ 21 ], and Sub-Saharan Africa [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 240 , 248 , 249 The ASPs are widely recognized as competent planning and policy implementation mechanisms to battle AMR’s mounting threat. 79 , 250 , 251 There is also the widespread belief that antimicrobial stewardship is a team’s determination to comprise all healthcare workers in the continuum of care. ASPs may vary by healthcare institutions; therefore, flexible and tailored approaches to local needs are essential.…”
Section: Professionals Annotationmentioning
confidence: 99%